Acoustic hysteresis in flows with different kinds of relaxation and attenuation - Anna Perelomova (Archives of Acoustics, 2022)
Graphs in the thermodynamic plane acoustic pressure versus excess acoustic density representing acoustic hysteresis, are considered as indicators of relaxation processes, equilibrium parameters of a flow, and kinds of wave exciters. Some flows with deviation from adiabaticity are examined: the Newtonian flow of a thermoconducting gas, the flow of a gas with vibrational relaxation, the flow of liquid electrolyte with a chemical reaction, and the Bingham plastic flow. The total range of characteristic frequencies of a harmonic exciter is taken into account. The impulsive sound is considered as well. The peculiarities of hysteretic behaviour are discussed in dependence with the kind and degree of deviation form adiabaticity. Examples of acoustically active flows are discussed.